Strategi Guru Bimbingan dan Konseling dalam Mengatasi Ketidakdisiplinan Siswa di MTs Nurul Huda Banjar Agung - Aliqma Mutiara Zamil (Jurnal Konseling dan Psikologi Indonesia, 2026)
This study aims to describe the forms of student indiscipline, identify the strategies used by Guidance and Counseling (BK) teachers in handling these problems, and analyze the effectiveness of their implementation at MTs Nurul Huda Banjar Agung. The study uses a qualitative approach with observation, interview, and documentation techniques. Data analysis was conducted through reduction, presentation, and conclusion drawing with validation through source triangulation. The results showed that forms of student indiscipline included tardiness, incomplete school supplies, not doing school assignments, and disorderly behavior during the learning process. The contributing factors were internal, such as low motivation to learn, and external, such as lack of parental supervision and environmental conditions. The guidance counselor's strategies included a persuasive approach, individual counseling, light assessment of student behavior, commitment to change, and cooperation with homeroom teachers and parents. These strategies proved to be quite effective because they were able to produce gradual behavioral changes through a humanistic approach and consistency in their implementation. This study emphasizes the importance of the role of guidance counselors in developing student discipline through comprehensive interventions involving various parties.